Impact of IL28B, ITPA and PNPLA3 genetic variants on therapeutic outcome and progression of hepatitis C virus infection. (July 2015) - Rembeck, Karolina; Lagging, Martin
Chronic HCV infection comprises a broad spectrum of liver disease, ranging from no or minimal activity to active hepatitis that in time may progress to severe liver fibrosis, cirrhosis and hepatocellular carcinoma if left untreated. This review describes the impact of genetic variants of interleukin 28B ( IL28B ; also known as interferon-lambda 3), inosine triphosphate pyrophosphatase ( ITPA ) and patatin-like phospholipase domain-containing 3 ( PNPLA3 ) on therapeutic outcome and liver disease severity in HCV-infected patients.